Development and Optimization of Luliconazole Nanostructured Lipid Carriers Based Gel by Quality by Design its Skin Distribution Studies, Dermatokinetic Modeling & In-Vitro and Ex-Vivo Correlation - Bhargav, Eranti; Reddy, Yiragamreddy P.; Koteshwara, Kunnatur B (Current Drug Delivery, 2021)
Aim: The present study was aimed to improve the permeability of Luliconazole (LZ) and to localize high drug concentrations at skin layers by Quality by Design (QbD) based Nanostructured lipid carriers (NC) based gel. Methods: Quality Target Product Profile was set, and Critical Quality attributes were identified. FT-IR and DSC studies confirmed compatibility. Risk assessment was carried out by screening the factors using 2IV7-2 fractional factorial design and optimization by Box Behnken design. Cholesterol: Cetyl Palmitate, PEG 200 and probe sonication time were identified as factors, Particle size (<200 nm), PDI (0.4), % Entrapment efficiency (% EE, >80%) and % Cumulative Drug release (% CDR, >95%) as responses. Contour plots, overlay plots and desirability, were utilized to create design space. Results: The quadratic polynomial equations showed increased lipid content, PEG 200 and optimum sonication time reduced particle size, PDI, improved % EE and % CDR. The optimized formula was formulated into a gel. Ex-vivo permeation studies performed using pig ear pinna skin revealed that developed LZ NC gel exhibited greater permeation 272.98±8.57 (μg/cm2) and 32.11 ±4.7 (μg/cm2/h) flux than plain drug dispersed gel. Dermatokinetic parameters of LZ NC gel revealed that a highly significant amount of LZ was permeated, distributed and transported through the skin layers. The better linear correlations were obtained by LZ permeation through a synthetic membrane (in-vitro) and pig ear pinna skin (ex-vivo). Conclusion: The above findings revealed that developed LZ NC gel exhibited better permeation and localization at skin layers in treating fungal infections.
Keywords: ex– vivo permeation